Increasing Childhood Influenza Vaccinations at the Community Pharmacy in Pennsylvania: Important Factors to Parents and Their Peers-A Pilot Study - Danielle Mayer; Melissa Frontino; Patricia Melissen; Daohai Yu; Nima PatelShori (University of Minnesota Libraries Publishing, 2018)
Objective: The primary objective was to identify factors that would motivate an adult to bring a child into the community pharmacy for an influenza vaccination via a pilot study conducted in Pennsylvania. Design: This was a multi-site, cross-sectional, exploratory, survey-based pilot study. Setting: Participants were identified at three grocery store community pharmacies in southeastern Pennsylvania. Results: A total of 349 surveys were collected over the study period and 325 participant surveys were included in the analysis. Receiving a vaccine in fifteen minutes or less (140; 74%) and not needing an appointment (142; 75%) were the top motivating factors for parents. Privacy, increased knowledge, and pharmacist counseling were identified as motivating factors for ninety-five (51%), eighty-nine (48%), and eighty-four (45%) parents, respectively. Cost was a barrier for eighty-eight parents (47%).The motivators and barriers for peers, those without children who might influence a parental decision, were similar to those of parents, however, more peers identified a child friendly environment (45% vs. 32%; p=0.02) and pharmacist counseling (57% vs. 45%; p=0.03) as motivators. Conclusion: The opportunity to receive an influenza vaccination quickly, without an appointment, are the most important factors to parents and peers. Factors of cost, counseling, and increased access to educational materials are of moderate importance.   Conflict of Interest: None Treatment of Human Subjects: IRB exemption granted   Type: Original Research